Caracterização e tratamentos de efluentes gerados no uso de tinturas capilares - Rodrigues, Jaqueline Cavalheiro (2020)
The concern with environmental issues encourages research in order to propose more efficient ways of treating effluents. Among these, the effluents from beauty salons stand out due to the high concentration of hair dyes. Despite this, there are few studies that propose treatment methods for this type of effluent in real conditions. The objective of this study is to characterize the effluents of beauty salons. Evaluate and propose treatments that minimize their impact when discharged into domestic sewage and can be applied in a decentralized manner. Different hair dye effluents were characterized in beauty salons in Porto Alegre, showing high concentrations of BOD, total solids and turbidity. Through analyzes, it was possible to verify that this effluent is more complex than domestic ones. The effluent of the most consumed dye has a brown tint and it was submitted to studies of adsorption, Fenton, photo-Fenton, ozonation and photolysis. Studies of adsorption of the effluent with activated charcoal (5 mg.mL-1) at room temperature showed better results than the effluent subjected to heating at 60 °C, with a 95% reduction in turbidity, 85% of the absorbance related to the organic matter in 254 nm and 279 nm, 79% at 413 nm and 82% at the 508 nm wavelength characteristic of the paraphenylenediamine compound. The ozonation treatment proved to be inefficient, considering the interference of the foam formed due to the composition of the effluent and the need to add defoamer. The photo-Fenton process showed better results compared to Fenton, with 99.9% of turbidity eliminated, 84% reduction in absorbance values for all analyzed wavelengths (254, 279, 413 and 508 nm), and mineralization rate of 44%. The photolysis process for 60 minutes reduced the turbidity by 98%, the BOD values by 76%, the total solids content by 31% and the absorbance values at 254 nm by 88%, at 279 nm by 87%, at 413 nm by 94% and at 503 nm by 95.4%. Photolysis processes with alteration of the effluent pH, which is close to neutrality, did not present more significant values, both acidic and basic, when compared to the study in natural pH. Also a previous heating of the effluent and a larger photolysis time did not present improvements, showing fluctuations in the results and reduced efficiency, probably due to reactions of by- 23 products that are formed during the process. The studies showed the variability of organic compounds present in hair dye effluents, the importance of this proposal and the need for further research. It was found that the photolysis process could be implemented in a decentralized manner in relation to the other processes, considering the ease of operation and maintenance in relation to the other studied processes.